1988
DOI: 10.1113/jphysiol.1988.sp016921
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanism of fade of gastrin‐stimulated gastric acid secretion in the cat.

Abstract: SUMMARY1. In conscious cats prepared with gastric fistulae gastric acid secretion in response to pentagastrin was found to reach a maximum after 45 min of stimulation, and to fade thereafter. Over the period 45-150 min of stimulation the fade was 5-4-7-8 % of the maximum response per 15 min.2. Once the response to pentagastrin had declined, acid secretion could not be restored by doubling the dose of pentagastrin, although an equisecretory dose of histamine could restore it.3. Low doses of histamine were addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The rate of fade of the pentagastrin response expressed as a percentage of the peak response was not related to the dose of pentagastrin, declining at about 36% 16min-. This value is considerably greater than values, 4.6-7.8% 15min'1, obtained for the decline of acid secretion in the anaesthetized and conscious cat and conscious rat (Reed & Smy, 1976;Albinus et al, 1977;Hirst et al, 1978;EmAs et al, 1981;Hirst, 1988). The fade of the response in vitro is unlikely to be explained by depletion of an essential nutrient.…”
Section: Mechanisms Offade and Tachyphylaxismentioning
confidence: 54%
See 4 more Smart Citations
“…The rate of fade of the pentagastrin response expressed as a percentage of the peak response was not related to the dose of pentagastrin, declining at about 36% 16min-. This value is considerably greater than values, 4.6-7.8% 15min'1, obtained for the decline of acid secretion in the anaesthetized and conscious cat and conscious rat (Reed & Smy, 1976;Albinus et al, 1977;Hirst et al, 1978;EmAs et al, 1981;Hirst, 1988). The fade of the response in vitro is unlikely to be explained by depletion of an essential nutrient.…”
Section: Mechanisms Offade and Tachyphylaxismentioning
confidence: 54%
“…Tachyphylaxis, the phenomenon of progressively reduced responses upon repeated stimulation by the same secretagogue, of pentagastrin-stimulated acid secretion has also been observed in the rat isolated stomach and gastric mucosa (Bunce et al, 1976;Main & Pearce, 1978). Fade and tachyphylaxis are common to all gastrin peptides (Hirst et al, 1978;Hirst, 1988). Studies in the cat in vivo have indicated that fade of the acid secretory response to gastrin may be related to release of an inhibitor (Izzat & Waton, 1987), a limiting gastric mucosal blood flow (Reed & Smy, 1976), and/or inactivation or desensitization of gastrin receptors (Albinus et al, 1977;Hirst et al, 1978;Hirst, 1988).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations